The Influence of Investment Opportunity Set and Profitability On Dividend Policy of LQ-45 Companies Listed On The IDX - Adziem, Faidul; Masrullah, Masrullah; Sukara, Salsabila (INVOICE : JURNAL ILMU AKUNTANSI, 2024)
The size of the dividend to be distributed by the company depends on the policies of each company. Companies in receiving investment from investors usually use Investment Opportunity Set (IOS) decision proxies. In addition, investors sometimes look at the percentage level of the company's profitability in order to assess the level of profit that the company gets before making an investment. This study aims to obtain empirical evidence of the effect of Investment Opportunity Set (IOS) and Profitability on Dividend Policy. The population in this study are companies that are included in the LQ-45 for the 2019-2021 period. The sample was selected using purposive sampling in order to obtain 21 observation samples. The analysis technique used in this study uses a panel data regression model using the SPSS version 25 research tool. The results of this study indicate that Investment Opportunity Set (IOS) has no significant effect on Dividend Policy with a significance value of 0.6450.05. As for Profitability, it has a significant effect on Dividend Policy with a significance value of 0.010 0.05